CHI3L1 on fibrinolytic system imbalance in chronic rhinosinusitis with nasal polyp - Yang, Hyun-Woo; Park, Joo-Hoo; Shin, Jae-Min; Son, Hyeong-Guk; Kim, Tae-Hoon; Lee, Seung-Hoon; Park, Il-Ho (Frontiers in Immunology, 2024)
Background: Chronic rhinosinusitis (CRS) is an inflammatory disease affecting more than 10% of the global adult population. It is classified into Th1, Th2, and Th17 endotypes and eosinophilic and non-eosinophilic types. Th2-based inflammation and eosinophilic CRS (ECRS) are associated with tissue remodeling and fibrinolytic system impairment.Objective: To elucidate the role of eosinophils in inducing fibrin deposition in CRS nasal polyp tissues and explore potential regulatory mechanisms.We analyzed the expression of genes related to the serpin family and fibrinolytic system using Gene Expression Omnibus and Next-generation sequencing data. Differentially expression genes (DEGs) analysis was used to compare control and nasal polyp tissues, followed by KEGG and Gene ontology (GO) analysis. We measured the expression and correlation of plasminogen activator-1 (PAI-1), tissue plasminogen activator (t-PA), urokinase plasminogen activator (u-PA), and urokinase plasminogen activator surface receptor (u-PAR) in CRS tissues, and evaluated the effect of eosinophils on the fibrinolytic system using a cytokine array and co-culture.Results: Nasal polyp tissues showed upregulated PAI-1, u-PA, and u-PAR expression and downregulated t-PA expression. Fibrinolytic system-related genes positively correlated with Th2 cytokines, except for t-PA. Eosinophil-derived Chitinase-3-like protein 1 (CHI3L1) increased PAI-1 expression and decreased t-PA levels in fibroblasts and epithelial cells. The inhibition of CHI3L1 suppresses these alterations.CHI3L1 contributes to fibrin deposition by impairing the fibrinolytic system during nasal polyp formation. The regulation of CHI3L1 expression may inhibit fibrin deposition and edema in ECRS, presenting a potential treatment for this condition.